1994
DOI: 10.1063/1.112837
|View full text |Cite
|
Sign up to set email alerts
|

Formation of artificial BaTiO3/SrTiO3 superlattices using pulsed laser deposition and their dielectric properties

Abstract: We have formed strained dielectric superlattices of BaTiO3 (BTO) and SrTiO3 (STO) by a pulsed laser deposition technique. A large strain of 400–500 MPa is introduced at the interface between the BTO and STO layers. A large dielectric constant of 900 was observed with a stacking periodicity of 2 unit cells/2 unit cells. The superlattices show drastically different electrical behavior from that of the solid solution (Sr,Ba)TiO3 films. Broad maxima of the dielectric constants occur around 40–50 °C and the values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
231
2
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(246 citation statements)
references
References 16 publications
11
231
2
2
Order By: Relevance
“…[1][2][3][4][5][6][7] For example, enhanced FE and dielectric properties could be achieved in SLs composed of FE BaTiO 3 (BTO) and paraelectric (PE) SrTiO 3 (STO) layers. 1,2,6,8 Such enhancement of ferroelectric polarization is known to originate from the strong strain coupling of ferroelectric polarization in BaTiO 3 -based ferroelectrics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] For example, enhanced FE and dielectric properties could be achieved in SLs composed of FE BaTiO 3 (BTO) and paraelectric (PE) SrTiO 3 (STO) layers. 1,2,6,8 Such enhancement of ferroelectric polarization is known to originate from the strong strain coupling of ferroelectric polarization in BaTiO 3 -based ferroelectrics.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] For example, enhanced FE and dielectric properties could be achieved in SLs composed of FE BaTiO 3 (BTO) and paraelectric (PE) SrTiO 3 (STO) layers. 1,2,6,8 Such enhancement of ferroelectric polarization is known to originate from the strong strain coupling of ferroelectric polarization in BaTiO 3 -based ferroelectrics. 9,10 Recently, by including PE CaTiO 3 (CTO) layers, three-component SLs have been designed and raised an intriguing issue of artificially broken compositional inversion symmetry, 11,12 resulting enhanced ferroelectric properties.…”
mentioning
confidence: 99%
“…In ideal superlattices with perfectly flat, compositionally abrupt interfaces, first-principles calculations and experimental studies have shown how factors such as strain due to lattice mismatches 1,2,3,4,5,6,7,8,9,10,11,12,13,14 , charge compensation 15,16,17,18 and bonding at the interface 19 can be controlled to enhance the ferroelectric properties of the superlattice. Work by Dawber and coworkers show that the behavior of very short period superlattices may deviate from that extrapolated from longer periods 11 .…”
mentioning
confidence: 99%
“…Some research groups have succeeded in fabricating perovskite type artificial superlattices [1 -5]. An anomaly of dielectric properties in BaTiO 3 /SrTiO 3 (BTO/STO) superlattice was pointed out by Tabata et al [3] and Nam et al [4]. However, the dielectric properties of BTO/STO superlattices are still not very reliable because superlattices made in an ultra-high vacuum system usually show high-leakage currents.…”
Section: Introductionmentioning
confidence: 99%